Interactive Meaning in The Photo Series “The Pancasila Values Implementation in Daily Communal Life”: A Visual Grammar - Nugroho, Yusri Estu; Kurniawan, Muhammad Hafiz (Modality Journal: International Journal of Linguistics and Literature, 2024)
This analysis focuses on the interactive meaning within the visual narratives of the photo series "Penanaman Nilai Nilai Pancasila dalam Kebersamaan Sehari Hari", through the lens of visual grammar analysis. Grounded in Kress and van Leeuwen's framework of visual semiotics, the study investigates how images in the series construct social interactions and convey ideological messages related to the values of Pancasila in daily communal life. The analysis focuses on representational, interactive, and compositional meanings, with particular emphasis on the interactive dimension, exploring the role of gaze, framing, and perspective in fostering viewer engagement and promoting relational meanings. Findings reveal the subtle yet powerful ways in which everyday scenes can embody and transmit cultural ideologies. This research contributes to the understanding of visual communication in reinforcing national identity and values, offering insights into the role of imagery in social cohesion within the Indonesian context. This research contributes to a deeper understanding of how visual media can serve as a tool for ideological dissemination and societal cohesion, reflecting the ongoing importance of Pancasila as a guiding principle in Indonesian life. Abstrak Analisis ini berfokus pada makna interaktif dalam narasi visual seri foto “Penanaman Nilai-nilai Pancasila dalam Kebersamaan Sehari-hari”, melalui lensa analisis tata bahasa visual. Dengan berlandaskan pada kerangka semiotika visual Kress dan van Leeuwen, penelitian ini menyelidiki bagaimana gambar-gambar dalam seri foto tersebut mengkonstruksi interaksi sosial dan menyampaikan pesan-pesan ideologis yang berkaitan dengan nilai-nilai Pancasila dalam kehidupan bersama sehari-hari. Analisis ini berfokus pada makna representasional, interaktif, dan komposisi, dengan penekanan khusus pada dimensi interaktif, mengeksplorasi peran tatapan, pembingkaian, dan perspektif dalam mendorong keterlibatan pemirsa dan mempromosikan makna relasional. Temuan-temuan mengungkapkan cara-cara yang halus namun kuat di mana adegan sehari-hari dapat mewujudkan dan mentransmisikan ideologi budaya. Penelitian ini berkontribusi pada pemahaman komunikasi visual dalam memperkuat identitas dan nilai-nilai nasional, menawarkan wawasan tentang peran citra dalam kohesi sosial dalam konteks Indonesia. Penelitian ini berkontribusi pada pemahaman yang lebih dalam tentang bagaimana media visual dapat berfungsi sebagai alat untuk penyebaran ideologi dan kohesi sosial, yang mencerminkan pentingnya Pancasila sebagai prinsip panduan dalam kehidupan Indonesia. Kata Kunci: keyakinan, pelajar, grammar, pengajaran bahasa inggris